Knowledge and Attitude Regarding Sleep Medicine among Medical Students at Qassim University, Saudi Arabia - Alrebdi, Yazeed Mohammad (Open Access Maced J Med Sci, 2019)
BACKGROUNDS: Sleep disorders and sleep medicine are underrecognized by both the general public and health care workers. Lack of education and training in sleep medicine has resulted in a culture of physicians who have very limited knowledge about sleep disorders and, as a result, are likely to underdiagnose and under-treat patients. AIM: This study aimed to assess the knowledge of and attitude regarding sleep medicine among medical students at Qassim University. METHODS: This was a cross-sectional study of 4(th) and 5(th)-year medical students, conducted at Qassim University (Central and Unaizah branches), Saudi Arabia. We used a self-administered data collection tool to collect personal information (age, name, sex, medical school), and assessed general attitude toward sleep medicine and the students’ current knowledge about sleep medicine using the Assessment of Sleep Knowledge in Medical Education (ASKME) survey. RESULTS: The prevalence of medical students who had a special interest in sleep medicine was 23.3%. Poor knowledge about sleep medicine was detected in 94.8% of students, while good knowledge was observed in only 5.2%. The attitude of the students toward sleep medicine was negative among 40.5% and positive among 59.5%. University branches, gender, and preferred speciality were all significantly associated with attitude score, whereas interest in sleep medicine and knowledge of sleep disorders were associated with both knowledge and attitude scores. CONCLUSION: This study found that medical students’ knowledge of sleep medicine was very low, despite the majority of them having a positive attitude toward it.